Reading comprehension in digital and printed texts - Alisaari J.; Turunen T.; Kajamies A.; Korpela M.; Hurme T.-R. (Netherlands, 2025)
Recent studies have yielded contradictory results regarding how reading from print or from the screen influences reading comprehension. This study examined 12-year-old students’ (N = 142) reading comprehension using printed text and digital text. The results indicated that performance was similar for printed text and digital text, even when gender, decoding skills, preference for school tasks on paper, screen, or both, and self-concept as a reader and computer user were controlled for. Regardless of the reading medium, students with better decoding skills and a higher self-concept as a reader performed better, boys outperformed girls, and students equally willing to study with books and computers outperformed students who preferred computers. The results of this study highlight the benefits of flexible use of both printed texts and digital texts for reading comprehension. As students are getting as used to studying via computers as they are to studying from books, the emphasis on the medium of studying seems to become less important. The topic of this study is of great relevance in a modern school context where ICT use has become a part of daily schoolwork worldwide.